Athletes` performance in different boulder types at international bouldering competitions - Augste, C.; Sponar, P.; Winkler, M. (International Journal of Performance Analysis in Sport, 2021)
The purpose of the study was to analyse the occurrence of different boulder types and the athletes` success rates in international competitions to contribute to the performance structure of competitive bouldering. Therefore, we classified 448 boulder sections of the final rounds of 14 Bouldering World Cups 2017 and 2018 using video analysis. We conducted analysis of frequencies, chi-square tests, binomial regressions and ANOVA for the respective analysis with regard to gender, competition round, wall section, and athlete level. In more than half of the boulder sections the crux was a dynamo. We found no differences between men and women in the occurrence of the different boulder types. Men solved significantly more boulder problems than women in the categories dynamo and mantle. Women were significantly more successful with slab problems. Lower ranked female athletes were significantly worse than the top 20 athletes in the dynamo, volume, and crimp categories, whereas men were worse in the categories dynamo, and slab. Our findings suggest that the training focus for athletes at international level should be on optimising dynamic moves. For female athletes, maximum strength of fingers and arms is more crucial for maximum achievement in competitive bouldering than for male athletes.